Evaluating post-fire geomorphic change on paired mulched and unmulched catchments using repeat drone surveys - Hayter, Lindsey, author; Nelson, Peter, advisor; Kampf, Stephanie, committee member; Morrison, Ryan, committee member (Colorado State University. Libraries, 2023)
Sediment redistribution after wildfire can dramatically alter a catchment and pose risks to local infrastructure and water quality. Mulch application is increasingly being used to mitigate post-fire hillslope runoff and erosion, although relatively little is known about its effects at the catchment scale. In this study we used repeat drone surveys to measure erosion and deposition across 6 small (0.5-1.5 km2) catchments, 3 mulched and 3 unmulched, in the 2020 Colorado Cameron Peak Fire burn scar. The objectives were to (1) quantify sediment volumes and spatial patterns of erosion and deposition on a catchment and channel scale, (2) compare geomorphic change to mulch coverage, vegetation cover, precipitation intensity, burn severity, and morphologic metrics, and (3) identify conditions in which mulch may be most appropriate based on findings. Initial drone surveys were gathered in the spring of 2022 shortly after mulching and were differenced to surveys collected in fall of 2022, capturing the erosional effects of a Colorado monsoon season within a 6.4 cm horizontal resolution DEM of Difference (DoD). Structure from motion (SfM) errors were thresholded out of the DoD to yield maximum and mean levels of detection at 14 cm and 5 cm respectively. Vegetation was filtered from the DoD by supervised classification of vegetation in the drone imagery. We found hillslope erosion dominated the sediment budget, with the mulched catchments eroding 141% more per area than the unmulched. A regression model suggested erosion to be most influenced by vegetation, hillslope length, and maximum 60-minute rainfall intensity. Channels were overall net depositional, and patterns of erosion and deposition in channels were controlled by changes in slope and stream power as well as local morphologic metrics. Our analysis does not find a significant impact of mulch at the catchment scale especially when coverage is low (~22%) and highlights the importance of understanding catchment attributes and processes when making post-fire treatment decisions.